Nominalisierung in Abstracts deutscher und polnischer sprachwissenschaftlicher Artikel - Adam Gołębiowski (Beiträge zur Allgemeinen und Vergleichenden Sprachwissenschaft)
The aim of this study is to analyze and compare the use of nominalized verbs and adjectives in abstracts of research articles in linguistics written by German- and Polish-speaking scientists. The paper begins by describing academic texts as a subject of (comparative) linguistic investigation. The next section focuses on structure and pragmatic features of abstracts as components of research articles. Subsequently the role of nominalization as one of the strategies of syntactic compression (also called syntactic condensation) and as an element of nominal style in academic texts is discussed. The next part presents the results of qualitative analysis of the data gained from 20 German and 20 Polish abstracts of research articles in linguistics. The concluding section 6 sums up the presented study and offers some recommendations for further research.